(untitled) (Международный научный журнал «Инженер», 2026)
In this article, studies of the stress-strain state of pipes made of polymer materials interacting with the soil under seismic influences were conducted. To solve such a problem, the equations of motion of underground pipelines with corresponding initial, boundary, and contact conditions were derived. The interacting "pipeline-soil" system is considered as a two-layer cylinder, the first layer of which is the soil, and the second is the pipeline. Assuming that a seismic wave propagates in the soil in the direction of the pipeline axis, the equations of motion of the interacting "pipeline-soil" system have been derived. Changes in the pressure of the soil on the pipeline, as well as the stress-strain state of the pipeline and the surrounding soil under conditions of rigid contact or contact, taking into account the movement of the pipeline relative to the soil, depending on the physical and mechanical properties of the soil, the coefficient of interaction of the structure with the soil, the depth of the pipeline and its geometric dimensions, as well as the direction of seismic forces, were investigated.